A Study on Total Volatile Organic Compound Emission of Plywood: Finish, Age, and Environment - Dia, Erika Vixeen; Bo-ot, Luis Maria (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment, 2020)
In this paper, actual emissions of total volatile organic compounds (TVOCs) of Philippine plywood were measured. The measurements were taken with the plywood having different finishes during the time period of May to October. The finishing considered was unpainted panels of plywood, newly painted with regular and green-labelled paint, and the readings were conducted in a controlled room with accompanying readings of temperature and relative humidity. Each set of test samples was measured every hour for seven straight days and compared to guideline emission and behaviour of TVOC in plywood in other countries. This study can contribute as a baseline data for the TVOC emissions of a Philippine building material.